2016
DOI: 10.18203/2320-1770.ijrcog20161704
|View full text |Cite
|
Sign up to set email alerts
|

Case series of abdominal sacral colpopexy

Abstract: INTRODUCTIONAbdominal sacral colpopexy was introduced in early 1960s, it become a widely accepted trans abdominal procedure that suspends the vaginal vault to the sacrum using natural or synthetic grafts.1 Abdominal sacral colpopexy attaches the vaginal vault to the sacral promentary and restores the physiological position of the vagina According to the International continence society, descent of the vaginalapex/ cuff /vaginal vault below a point that is 2 cm less than the total vaginal length above the plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…14 Similar finding also seen in Monika Anant et al, Dhama et al in their respective studies. 11,15 Nygaard et al concluded that sacrocolpopexy is a reliable procedure that effectively and consistently resolves vaginal vault prolapse. Patients should be counseled about the low, but present risk, of reopening for prolapse, stress incontinence, and complications.…”
Section: Resultsmentioning
confidence: 99%
“…14 Similar finding also seen in Monika Anant et al, Dhama et al in their respective studies. 11,15 Nygaard et al concluded that sacrocolpopexy is a reliable procedure that effectively and consistently resolves vaginal vault prolapse. Patients should be counseled about the low, but present risk, of reopening for prolapse, stress incontinence, and complications.…”
Section: Resultsmentioning
confidence: 99%